Kinome analysis of Madurella mycetomatis identified kinases in the cell wall integrity pathway as novel potential therapeutic drug targets in eumycetoma caused by Madurella mycetomatis - Konings, Mickey; Strepis, Nikolaos; Manabe, Ri-Ichiroh; Hasegawa, Akira; Chaudhari, Somdatta; du Pré, Saskia; Schippers, Marij; Tagami, Michihira; Ma, Jingyi; Okazaki, Yasushi; Todd, Matthew; Biersack, Bernhard; et al. (PLoS neglected tropical diseases, 2025)
Eumycetoma is a neglected tropical subcutaneous disease most commonly caused by the fungus Madurella mycetomatis. Currently, eumycetoma is treated by a combination of antifungal therapy and surgery, with limited success rates. To identify novel drug targets we used an in silico approach to determine the kinases present in M. mycetomatis genome and rank them as potential drug targets. In total 132 predicted kinases were identified in M. mycetomatis , of which 21 were predicted to be essential for fungal viability and 4 of these had no human orthologues. Two were linked to the Cell Wall Integrity (CWI) signalling pathway and were expressed in a Galleria mellonella infection model. Several kinase inhibitors were identified after in silico modelling, however only 8 were able to inhibit growth. Five had predicted binding affinity with components of the CWI. Altogether, the CWI shows potential as a drug target for further evaluation.